The Impact of Architectural Design on Reducing Anxiety in Schizophrenic Patients: Exploring Familiar Cognitive Patterns in Therapeutic Spaces - Baghbahadorani, Mohammad Kaveh; Ameri Siyahoyi, Hamidreza; Fooladi, Vahdaneh (Health Nexus, 2024)
This study investigates the impact of architectural design, specifically incorporating familiar cognitive patterns, on reducing anxiety levels in schizophrenic patients. Utilizing a mixed-methods approach, 30 patients from the Omid-e-Farda Center were assessed using the Hamilton Anxiety Rating Scale (HAM-A) before and after exposure to images of designed spaces. The findings demonstrated significant reductions in anxiety levels across all stages of intervention. After viewing Image A, the mean difference in anxiety levels was 21.57 (t(29) = 17.9, p < .001). Viewing Image B resulted in a mean difference of 29.57 (t(29) = 8.46, p < .001), and Image C led to a mean difference of 41.17 (t(29) = 11.17, p < .001). These results suggest that integrating familiar elements in therapeutic environments can significantly enhance psychological well-being and reduce anxiety in patients with schizophrenia. The study underscores the potential for interdisciplinary approaches in architectural design to improve mental health outcomes in clinical settings.